Application of rock brittleness evaluation in tight oil exploration—— Taking Lijiaweizi Fault Depression in Qijia Area as an Example. Issue 4 (April 2020) - Zeqiang, Wang; Yunfeng, Zhang; Bo, Sun
Abstract: Brittle rock is one of the key factors in the use of unconventional oil and gas exploration technology to be considered, The stronger the brittleness of rock is, the easier to produce fractures to form fracture network in the over flushing of fracturing, the stock of oil and gas storage layer will be increased, and the production of single well will be increased. At present mainly based on rock elastic parameters, we use Young's modulus and Poisson's ratio of two ways to analyze brittle rock in earthquake prediction evaluation. However, since these two methods in the process, both the need for elastic parameters of rock normalized, leading to large errors, adaptability reduce. Based on this, we propose a Young's modulus and Poisson's ratio coefficient of utilization of compared to the brittle rock evaluation method to effectively improve the accuracy of prediction and evaluation of brittle rock and anti-jamming capability, while the brittle evaluation method based on the use of pre-stack seismic inversion of elastic parameters to Qijia area of Songliao basin compact oil brittle rock predict deployment guidance wells to obtain stable high level of industrial oil flow.